Sycamore Lace Bug, Corythucha ciliata (Say) (Insecta: Hemiptera: Tingidae) - Susan E. Halbert; James R. Meeker (EDIS)
The sycamore lace bug, Corythucha ciliata (Say) is a native North American insect that feeds on sycamore trees (Platanus spp., especially Platanus occidentalis L.). The bugs feed on the undersides of the leaves, initially causing a white stippling that can eventually progress into chlorotic or bronzed foliage and premature senescence of leaves. In cases of severe infestations, trees may be defoliated in late summer. Several consecutive years of severe lace bug damage, combined with other stress factors, may kill the trees (Barnard and Dixon 1983). This document is EENY-190 (originally published as DPI Entomology Circular 387), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: February 2001.